Edukasi Literasi Digital Bijak Melalui Smartphone Dan Komputer Bagi Siswa SD - Salman Al Farisi; Enda Kartika Sari; Jum Dapi Okta (Universitas Dehasen Bengkulu, 2026)
The rapid advancement of digital technology has significantly influenced educational practices, including at the elementary school level. Smartphones and computers are increasingly accessible to students; however, improper and uncontrolled use may lead to negative impacts such as decreased learning focus, exposure to inappropriate content, and excessive screen time. This community service program aims to improve digital literacy and promote wise use of smartphones and computers among elementary school students in Batumarta II Village. The program employed an educational and participatory approach through interactive learning sessions, guided discussions, and practical demonstrations. Data were collected through observation, participant interaction, and reflective evaluation. The results indicate an improvement in students’ understanding of responsible technology use, digital ethics, and the ability to differentiate beneficial and harmful digital content. Students also demonstrated increased awareness of time management and appropriate digital behavior. This program highlights that early digital education is essential to shaping positive attitudes toward technology use. Sustainable collaboration between schools, parents, and community stakeholders is recommended to strengthen long-term digital literacy development among elementary school students.